Heavy haze episodes in Beijing during January 2013: Inorganic ion chemistry and source analysis using highly time-resolved measurements from an urban site - Han, Bin; Zhang, Rui; Yang, Wen; Bai, Zhipeng; Ma, Zhiqiang; Zhang, Wenjie (The Science of the total environment, 2016)
The heavy air pollution that occurred in Beijing in January of 2013 attracted intense attention around the world. During this period, we conducted highly time-resolved measurements of inorganic ions associated with PM2.5 at an urban site of Beijing, and investigated ion chemistry and potential sources. Hourly concentrations of Cl−, NO3−, SO42−, Na+, NH4+, K+, Mg2+, and Ca2+ were measured. Peak concentrations of SO42− and NO3− were observed on the 10th–15th, 21st–24th, and the 26th–30th during this monitoring campaign. The percentages of SO42− and NH4+ in total ion concentration increased with the enhancement of PM2.5 concentrations, indicating that high concentrations of SO42− and NH4+ may play important roles in the formation of haze episodes. The ratio of [NO3−]/[SO42−] was calculated, revealing that the sources of SO42− would contribute more to the formation of PM2.5 than mobile sources. Diurnal variations of SO42−, NO3−, NH4+ (SNA) exhibited a similar pattern, with high concentrations at night and low levels during the day, revealing that meteorological conditions, such as mixing layer height, relative humidity, were likely to be responsible for high levels of SNA at night. The roles of meteorological conditions were further discussed in the formation of secondary inorganic ions. Relative humidity and temperature played key roles and exhibited positive correlations with secondary inorganic ions. An aerosol inorganics simulation model showed that SNA existed mainly in the aqueous phase during the sampling period. Furthermore, potential sources were identified by applying positive matrix factorization model. Secondary nitrate, secondary sulfate, coal combustion and biomass burning, as well as fugitive dust, were considered to be major contributors to total ions. Variation of PM2.5 and ions concentrations in the sampling site in January 2013. The peak period of PM2.5 are marked between the dote lines (μg/m3). [Display omitted] •Sulfate was one of key reasons of heavy haze episodes Beijing.•RH and temperature played important roles in formation of SNA.•Coal/biomass combustion, secondary nitrate and sulfate were sources of heavy haze.